Students’ Hand-Washing Behaviour Based On Behavioral System Models as An Effort of Covid-19 Prevention - Risnah Risnah; Eny Sutria; Wahdaniar Wahdaniar; Muhammad Irwan (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
The most effective prevention of the spread of Covid-19 is to break the chain of transmission associated with the modes of transmission of Covid-19 by complying with health protocols. This study aimed to determine the handwashing behavior of nursing students based on Dorothy E. Johnson's theory as an effort to prevent Covid-19. The type of research was quantitative research with a descriptive method. The number of samples was 154 students using a proportionate stratified random sampling technique. The results showed that hand washing behavior in nursing students was in a good category as many as 62 respondents (40.3%), while the application of hand washing in the poor category was 32 respondents (20.8%). Based on the results of research with the application of Dorothy E Johnson's behavioral theory system, it is known that most students matched individual behavior with the demands and expectations that existed in society with a good category, the ability to adapt to various changes in body functions in the moderate category. Likewise, being productive and valuable for themselves and others in the moderate category, and the ability to provide solutions to other health problems was in the sufficient category. The majority of hand washing behavior in nursing students was in a good category, where the match between individual behavior and the demands and expectations that existed in society was in a good category as noticeable efforts to prevent Covid-19.